2007
DOI: 10.4103/0970-4388.37010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fluoride varnish on Streptococcus mutans counts in plaque of caries-free children using dentocult SM strip mutans test: A randomized controlled triple blind study

Abstract: The results showed that the study group had a statistically significant reduction in the plaque Streptococcus mutans counts than the control group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 10 publications
4
27
0
Order By: Relevance
“…These results can be due to antibacterial compounds present in each of them. Alginate contains fluoride, which is an antimicrobial factor (16). Fluoride prevents transformation of glucose inside bacteria and has destructive effects on energy production mechanisms, glucose synthesis and metalloenzymes (17).…”
Section: Discussionmentioning
confidence: 99%
“…These results can be due to antibacterial compounds present in each of them. Alginate contains fluoride, which is an antimicrobial factor (16). Fluoride prevents transformation of glucose inside bacteria and has destructive effects on energy production mechanisms, glucose synthesis and metalloenzymes (17).…”
Section: Discussionmentioning
confidence: 99%
“…Aside from the genetic and environmental factors that predispose a person to develop caries, the process itself does not occur without the existence of dental plaque or fermentable carbohydrates. Multiple studies have documented an association between an increase in number of S. Mutans in the saliva, dental plaque and increase in dental caries (2). Nowadays the serotypes of S. Mutans are considered the primary microorganism involved in caries formation, therefore correct control of S. Mutans levels is among the most important goals in the prevention and treatment of caries (3).…”
Section: Introductionmentioning
confidence: 99%
“…The cariogenic potential of S. mutans is manifested by the organism's ability to ferment various carbohydrates, producing large amounts of acid, and by its ability to participate in the formation of dental plaques. S. mutans is involved in the initial formation of the plaque biofilm through glucan formation [16]. Also; it has been shown that S. mutans contributes to dental caries [17].…”
Section: Introductionmentioning
confidence: 99%